İdari yargının görev alanının belirlenmesi sorunu - Çeken, Mesut (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Kamu Hukuku Anabilim Dalı, 2011)
Görev konusu; genel olarak bir yargı yerinin dava konusu yönünden uyuşmazlığın çözümünde yetkili olması anlamını taşımaktadır. Yargı sisteminin ya da bir yargı sistemi içinde yer alan yargı yerinin görev alanının belirlenmesi kamu düzeni ile ilgilidir. Bu nedenle de hiçbir yargı yeri görev alanı içinde olmayan bir davaya bakamayacağı gibi, kendi görev alanı içinde olan bir davaya bakmaktan da kaçınamaz. Uygulamada en fazla idari yargı ile adli yargı arasında görev uyuşmazlığı çıkmaktadır ki bu çalışmanın konusunun da ?idari yargının görev alanı? olması sebebiyle bu çalışmada idari yargının görev alanının belirlenmesi amaçlanmaktadır. Bu yapılırken ağırlıklı olarak başta Uyuşmazlık Mahkemesi olmak üzere yargı yerlerinin görev ayrımını yaparken geliştirdikleri kriterler üzerinde durulmakta ve sorunun temelinin anlaşılabilmesi bakımından ayrı bir yargı düzeni olarak idari yargının anayasal bir temelinin bulunup bulunmadığı tartışmasında başta Anayasa Mahkemesi olmak üzere yargı yerleri ile öğretideki görüşlere yer verilmektedir. İdari yargının görev alanının konu bazında tümüyle ortaya çıkarılmasının pek mümkün olmaması bir yana çalışmanın boyutlarını aşması nedeniyle görev uyuşmazlıklarına sebep olan belli başlı konular ele alındıktan sonra görevli yargı yerini gösteren yasaların buna ilişkin hükümleri ve son yıllarda idari yaptırımlar alanında görevli yargı yerinin belirlenmesi konusunu karmaşaya yol açan yasal gelişmeler -başta 5326 sayılı Kabahatler Kanunu olmak üzere- yargı kararları ışığında incelenmeye çalışılmaktadır
Duties judiciary administrative determination of the problem area
The subject matter of the jurisdiction, in general comes to mean a ruling position to be commissioned to seek a solution for the controversy in terms of the matter in dispute. Each Supreme Court with its sub-level courts constitutes a judicial system. The determination of a duty field of a judicial system or a ruling position in a judicial system is related to public order. As a consequence, no ruling position can rule a case that is out of its duty field and in the same way can avert from ruling a case that is related to its duty field. This as well is due for the principle of natural judge. In practice, the most controversy of duty comes out between the adjudication and the judiciary. As the topic is ?the duty field of adjudication?, this study aims at determining the duty field of adjudication. Meanwhile, the study dwells on -predominantly the Court of Jurisdictional Disputes- the criteria developed while segregating the duty field of ruling positions and touches on the ruling positions- predominantly the Supreme Court- and the sights in discipline in terms of the basis of the cause to be understood, the discussion whether the adjudication, as a separate judicial order, has a constitutional basis or not. Aside from the impossibility of the complete duty field of the adjudication to be introduced in point of case, by reason of the fact that it topped the limits of the subject focus, after tackling the certain issues that causes the controversy of duty, in this study, by assessing the terms of statues that indicate the ruling position in charge and the legit developments that convert the matter of determination of ruling position in charge on the area of administrative sanctions in recent years into an endless story ? predominantly the Offence Laws numbered 5326- which jurisdiction is responsible at the last point ranked, is tried to be defined in the light of the resolves of the Court of Jurisdictional Disputes.
Keywords: Görev alanı; Duty area; Yargılama; Judgement; Yargısal denetim; Judical rewiew; İdari işlemler; Administrative processes; İdari yargı; Administrative justice